Global Income and Employment Generation Impacts of Non-Timber Forest Products (NTFPs) and their Poverty Mitigation Potential: Reflections Based on Worldwide Evidences - Tewari, D. D.; Mahapatra, Ajay Kumar (Indian Forester, 2011)
Non-Timber Forest Products (NTFPs) generate sizeable magnitudes of income and employment in different parts of the world for the tribal and poor people. The evidence is based on the review of past studies across different continents. The study presents a collective evidence for the role of NTFPs in the economy of poor and downtrodden. NTFPs should be used as instrument for engendering economic development in low and underdeveloped sectors of the world.